2013
DOI: 10.1016/j.jpsychires.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of elevated cytokines with childhood adversity in a sample of healthy adults

Abstract: Objective Childhood trauma has been associated adult stress-related disorders. However, little is known about physiologic alterations in adults with a history of early life trauma that do not have current psychiatric or medical diagnoses. In this study, the relationships between childhood adversity and cytokine and C - reactive protein (CRP) levels in healthy adults were examined. Method Participants included men (n=18) and women (n=20) who did not meet DSM-IV criteria for Axis I psychiatric disorders or any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 72 publications
(82 reference statements)
0
52
0
Order By: Relevance
“…Hartwell et al (2013) found an important association of elevated basal cytokines with childhood adversity in a sample of healthy adults demonstrating the long-term impact of childhood trauma and stress on homeostatic systems. Importantly, this association was found in healthy adults, suggesting that these alterations may precede the development of significant stress-related psychiatric disorder or disease.…”
Section: Biological Consequences Of Parental Loss and Other Childhoodmentioning
confidence: 89%
“…Hartwell et al (2013) found an important association of elevated basal cytokines with childhood adversity in a sample of healthy adults demonstrating the long-term impact of childhood trauma and stress on homeostatic systems. Importantly, this association was found in healthy adults, suggesting that these alterations may precede the development of significant stress-related psychiatric disorder or disease.…”
Section: Biological Consequences Of Parental Loss and Other Childhoodmentioning
confidence: 89%
“…Parental separation in early childhood is also associated with increased CRP in adulthood (Lacey et al, 2013;McDade et al, 2013). Concentrations of IL-6, IL-1β, and TNF-α are elevated with childhood maltreatment (Gouin et al, 2012;Hartwell et al, 2013;Kiecolt-Glaser et al, 2011;Smith et al, 2011;Tietjen et al, 2012). Importantly, exposure to trauma in childhood is associated with increased risk for developing PTSD and other psychiatric conditions (Edwards et al, 2003).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…Similarly, early life stress has been linked with obesity, metabolic syndrome, cardiovascular disease and type 2 diabetes [1416]. Inflammation appears to be higher in adults exposed to early life adversity, including increased levels of interleukin-6 (IL-6), c-reactive protein (CRP), and tumor necrosis factor (TNF), which may further contribute to risk of cardiovascular disease [17, 18]. Adipokines, including leptin and adiponectin, are also dysregulated in individuals with high levels of childhood adversity [19].…”
mentioning
confidence: 99%